2019
DOI: 10.3390/atmos10120797
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Multiple UV-LIF Spectrometers Using the Aerosol Challenge Simulator

Abstract: Measurements of primary biological aerosol particles (PBAPs) have been conducted worldwide using ultraviolet light-induced fluorescence (UV-LIF) spectrometers. However, how these instruments detect and respond to known biological and non-biological particles, and how they compare, remains uncertain due to limited laboratory intercomparisons. Using the Defence Science and Technology Laboratory, Aerosol Challenge Simulator (ACS), controlled concentrations of biological and non-biological aerosol particles, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…The fungal samples used in this study are fungal material extracts intended for allergenic testing which have undergone chemical processing with acetone and are not naturally occurring whole spores. It is not clear how these may differ from naturally emitted spores, however, the fluorescent spectra of the processed samples are broadly consistent with those from other studies which examined live cultured fungal samples [23,38,40]. SEM images of the aerosolized fungal samples were made and these are presented in Forde et al, [23], where the samples were observed to be fibrous in nature and often amalgamated when rod-shaped or filament morphologies are expected.…”
Section: Acs Laboratory Datasupporting
confidence: 61%
See 4 more Smart Citations
“…The fungal samples used in this study are fungal material extracts intended for allergenic testing which have undergone chemical processing with acetone and are not naturally occurring whole spores. It is not clear how these may differ from naturally emitted spores, however, the fluorescent spectra of the processed samples are broadly consistent with those from other studies which examined live cultured fungal samples [23,38,40]. SEM images of the aerosolized fungal samples were made and these are presented in Forde et al, [23], where the samples were observed to be fibrous in nature and often amalgamated when rod-shaped or filament morphologies are expected.…”
Section: Acs Laboratory Datasupporting
confidence: 61%
“…A historic limitation of UV-LIF methods is that older spectrometers do not offer enough spectral resolution or morphological detail to unambiguously classify particles (e.g., Wideband Integrated Bioaerosol Spectrometer, WIBS and the UV-APS) due to the conflation of PBAP classes. More sophisticated UV-LIF spectrometers are now becoming available which offer much greater spectral resolution and particle shape information which should significantly improve PBAP classification capability [21][22][23][24][25]. While real time UV-LIF spectrometers may not offer the specificity of offline methods, their capacity for high time resolution detection makes them ideally suited for the investigation of rapid and dynamic changes in the indoor environment and as such provide critical complementary information on real-time dispersion.…”
Section: Pbap Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations